Women’s Involvement Pattern in Grain Management Activities in Deoghar District of Jharkhand (Indian Journal of Extension Education, 2024)
Post-harvest losses in India posed a significant challenge, resulting in food wastage, reduced income for farmers, and increased pressure on resources. In the context of agriculture and food security, women played a crucial role in post-harvest operations, performing tasks such as cleaning, sorting, drying, storage, processing, and marketing of agricultural products. The study was conducted in the year 2023 with a sample of 120 randomly selected farmwomen in the Deoghar district of Jharkhand. The study aimed to recognize the involvement pattern of farm women in various post-harvest activities in rural areas. The findings indicated major participation of farm women was in activities like the sowing of seeds (67.5%), decision-making regarding pre-storage treatment (66.7%), drying of threshed grains (60.8%), mid-storage/intermediate treatment of grains (60.8%) and drying before threshing (49.2%) etc. The study also highlighted various drying and storing related practices carried out by farm women like sun drying of grains, threshing of major cereal crops by beating etc. which were mostly manual job required heavy physical energy.